Nickel-molybdenum catalytic material, preparation method thereof and application of nickel-molybdenum catalytic material in electrolytic hydrogen production test

Through chemical corrosion treatment technology, the S-doped Ni/Fe (oxygen) hydroxide catalyst is formed on the nickel-molybdenum foam substrate, which solves the problems of high cost and unstable catalyst preparation in the prior art, and achieves efficient and stable redox electrocatalytic performance.

CN119571383APending Publication Date: 2025-03-07CHENGDU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411773150.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing electrochemical catalytic material preparation process has problems such as high cost, time-consuming preparation process, unfriendly environment, and unstable catalysts are prone to falling off.

Method used

Through chemical corrosion treatment technology, iron chloride hexahydrate and sodium thiosulfate pentahydrate act on a commercial nickel-molybdenum foam substrate was prepared from a supported S-doped Ni/Fe (oxygen) hydroxide catalyst to form a sheet crystal layer to expand the electrochemically active surface area.

Benefits of technology

The OER performance of high current density at low overpotential was achieved. The catalyst operated stably at 1A cm-2 industrial-grade current density for 1466 hours without significant attenuation of performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005170731370000061
    Figure BDA0005170731370000061
  • Figure BDA0005170731370000062
    Figure BDA0005170731370000062
  • Figure BDA0005170731370000071
    Figure BDA0005170731370000071
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochemical hydrogen production, and provides a nickel-molybdenum catalytic material and a preparation method thereof, and application of the nickel-molybdenum catalytic material in hydrogen production by electrolysis of water. According to the nickel-molybdenum catalytic material provided by the invention, the flaky crystals on the surface of the nickel-molybdenum catalytic material are tightly combined with the substrate, so that the problems that a catalyst is unstable in structure, easy to fall off and the like in the synthesis process of an OER catalyst are remarkably solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrochemical hydrogen production, and specifically relates to a nickel-molybdenum catalytic material and a preparation method thereof, as well as an application thereof in electrolytic hydrogen production testing. Background Art

[0002] Water electrolysis is a sustainable and clean route to produce hydrogen (H2) fuel, which is crucial for future renewable energy options. Water electrolysis consists of two main half-reactions: the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. Compared with the HER process, the OER process is much slower due to the rigid O-O double bond and the multi-step proton-electron transfer process, which greatly affects the overall efficiency of water splitting. In the past few years, in order to reduce the overpotential of OER, a lot of efforts have been invested in the development of efficient catalysts, including transition metal oxides, (oxy)hydroxides, selenides, phosphides and nitrides, which has largely accelerated the research and development of OER electrocatalysts.

[0003] Transition metal (oxy)hydroxides, especially nickel-iron-based (oxy)hydroxides, are the most effective of all candidate OER catalysts reported so far, and are also proven to be the real catalytically active species produced in the surface reconstruction of many types of oxygen-producing materials. At present, a large number of research efforts have been made to further improve the OER activity of nickel-iron-based (oxy)hydroxide catalysts through various strategies, such as exposing more active sites through morphology design, regulating the electronic structure through surface defect engineering, and improving the electrochemical catalytic activity through lattice oxygen mechanism. For example, Wu's team recently reported a defect that can improve the electrocatalytic performance of NiFe-LDH, which can provide 10 and 50 mA cm at an overpotential of only 230 and 290 mV. -2 Recently, Yang’s team reported a NiFe alloy-ultrathin amorphous oxide hydroxide (shell) nanowire array core-shell catalyst that exhibited excellent OER activity, reaching 500 and 1000 mA cm at ultra-low overpotentials of 248 and 258 mV, respectively. -2The high current density of 200 Å / min to meet industrial needs has greatly promoted the development of large-scale water electrolysis for hydrogen production. In recent years, in situ electrochemical oxidation of metal chalcogenides (S and Se) has been reported as a new strategy for making metal oxides as OER catalysts. It is worth noting that in these cases, the chalcogenides are believed to be completely converted into oxides, and the enhanced OER activity is attributed to the increase in electrochemical surface area / increase in defects and decrease in grain size during electrochemical oxidation compared with ordinary metal oxides. However, the nature of the active sites and the mechanism of enhanced OER catalysis are not fully understood. For iron-containing multimetallic (Ni, Mo, Co, etc.) oxides / (oxy)hydroxides, OH* intermediates tend to adsorb on FeOOH sites due to their stronger affinity, but too strong adsorption of OH* on Fe sites may affect their OER performance. In principle, partial substitution of O by S can reduce the valence state of Fe and optimize the absorption energy of the intermediates, thereby regulating the OER activity of the catalyst.

[0004] In this study, we developed a one-step surface engineering approach to fabricate a self-supporting S-doped Ni / Fe (oxy)hydroxide catalyst from commercial nickel-molybdenum foam (NMF) within 1 h. This ultrafast method effectively designs the surface of the nickel-molybdenum foam into a large surface area (oxy)hydroxide layer. In addition, during the reaction, S is simultaneously introduced into the surface and lattice of the Ni / Fe (oxy)hydroxide, which may adjust the valence state of Ni / Fe, optimize the absorption energy of OER intermediates, and form certain vacancies inside the catalyst, thereby improving the OER activity. The catalyst only needs an overpotential of 210 mV in 1 M KOH to reach 10 mA cm -2 The current density is greatly improved, which greatly improves the performance of nickel-molybdenum-based catalysts. Summary of the invention

[0005] Technical problems solved by the present invention:

[0006] It is used to solve the problems of high cost, time-consuming preparation process, environmental unfriendliness, and unstable and easy-to-fall-off catalyst in the existing preparation process of electrochemical catalytic materials.

[0007] The technical solution adopted by the present invention is:

[0008] First, the present invention provides a nickel-molybdenum self-supporting catalytic material.

[0009] The catalytic material uses 1M / L potassium hydroxide as electrolyte, utilizes a standard three-electrode configuration, uses a treated commercial metal substrate (nickel-molybdenum foam) as an anode, Hg / HgO as a reference electrode, and a platinum plate as a counter electrode. The commercial metal substrate (nickel-molybdenum foam) is treated by a CV method (voltage window of 0-1V vs. Hg / HgO), and then the substrate is rinsed with deionized water and dried in a 40°C oven.

[0010] The ratio of each element in the catalytic material was determined by TEM-mappling characterization. The atomic ratio of nickel, iron, molybdenum, oxygen and sulfur in the nickel-molybdenum catalytic material was 15-35:2-10:0-1:60-75:0-3. TEM-mappling characterization and SEM--mappling characterization were used previously. TEM-mappling characterization was finally used as the standard because: during the SEM test, the sample was mounted on a commercial nickel-molybdenum substrate, and the composition analysis of SEM was a micro-area detection of a specific area on the surface of the sample, so there may be a certain error. This error mainly comes from the interference of the substrate on the signal and the complexity of the surface level, so the measured element ratio may not fully represent the actual composition of the sample. In contrast, the TEM test used a processed sample and mounted it on a copper mesh for detection. The use of a copper mesh reduces interference with elemental analysis, and the results obtained are more reliable and accurate. Therefore, TEM-mappling is selected, which can provide higher resolution and more detailed element distribution information, and its results are generally considered to be more representative.

[0011] Second, the present invention provides a method for preparing the aforementioned nickel-molybdenum catalytic material, comprising the following steps:

[0012] The metal substrate is corroded by a treatment solution, and the treated metal substrate is used as a working electrode to obtain a nickel-molybdenum catalytic material through electrochemical treatment in a three-electrode system; the treatment solution includes ferric chloride hexahydrate and sodium thiosulfate pentahydrate.

[0013] According to some preferred embodiments, the nickel-molybdenum catalytic material is prepared by using 1 mol / L potassium hydroxide as an electrolyte, a standard three-electrode configuration, a commercial metal substrate (nickel-molybdenum foam) as an anode, mercury / mercuric oxide as a reference electrode, and a platinum sheet as a counter electrode, and treating the metal substrate (i.e., the treated metal substrate) by cyclic voltammetry (CV method) [voltage window of 0-1V (V vs. Hg / HgO)], and then rinsing the metal substrate with deionized water and drying it.

[0014] According to some preferred embodiments, the metal substrate is a nickel molybdenum foam substrate (NMF).

[0015] According to some preferred embodiments, in the treatment solution, the addition ratio of ferric chloride hexahydrate to sodium thiosulfate pentahydrate is 0.1 mol / L:0.05 mol / L.

[0016] According to some preferred embodiments, the corrosion treatment is carried out at 40° C. for 1 hour.

[0017] In the present invention, by using chemical corrosion treatment technology, ferric chloride hexahydrate and sodium thiosulfate pentahydrate are used to act on the metal substrate, so that a dense flaky crystal layer grows on the originally smooth substrate surface, thereby preparing an OER nickel-molybdenum catalyst.

[0018] Third, the nickel-molybdenum catalytic material provided by the present invention is used in the test of hydrogen production by electrolysis.

[0019] The nickel-molybdenum catalytic material provided by the present invention has the following advantages:

[0020] (1) The nickel-molybdenum catalytic material provided by the present invention has a distinct lamellar crystal layer, which significantly expands the electrochemically active surface area, provides more reactive sites, has excellent electrical conductivity, and strong interfacial bonding force, thereby providing excellent and stable OER performance.

[0021] (2) Taking the mixed solution of (0.1 mol / L ferric chloride hexahydrate + 0.05 mol / L sodium thiosulfate pentahydrate) at 40 °C to treat the nickel-molybdenum substrate, the CV activation treatment was performed at room temperature as an example. The -2 , 50mA cm -2 and 100mA cm -2 At a current density of 1.3 mol / L, the overpotentials were 217 mV, 245 mV, and 261 mV, respectively, which were better than those obtained by thermochemical treatment with only 0.1 mol / L ferric chloride hexahydrate (290 mV, 327 mV, and 343 mV) and that obtained by treatment with only 0.05 mol / L sodium thiosulfate pentahydrate (329 mV, 389 mV, and 423 mV). In the constant voltage polarization test, the nickel-molybdenum catalytic material was able to -2 It can work stably for at least 1466 hours under industrial-grade current density without obvious performance degradation. The above data all reflect that the nickel-molybdenum catalytic material provided by the present invention has excellent OER performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is the LSV test diagram of each test sample;

[0023] Figure 2 is the overpotential diagram of oxygen evolution reaction of each test sample;

[0024] Figure 3 This is the NMFeS stability test diagram;

[0025] Figure 4 It is the EIS comparison diagram of each test sample at a specific DC potential;

[0026] Figure 5 is the SEM image of NMFeS;

[0027] Figure 6TEM--mappling element distribution map of NMFeS. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0029] Example 1

[0030] The present embodiment provides a nickel-molybdenum catalytic material, and the preparation method includes the following steps: immersing untreated NiMo foam in a mixed solution containing 0.1 mol / L ferric chloride hexahydrate and 0.05 mol / L sodium thiosulfate pentahydrate, corroding at 40°C for 1 hour, using the corroded commercial nickel-molybdenum foam (NMF) (Kunshan Dingsheng Chemical Materials Co., Ltd., Ni:Mo=7:3) as the anode, Hg / HgO as the reference electrode, and platinum sheet as the counter electrode. Within the voltage window range of 0-1V (V vs.Hg / HgO), CV scans for several circles. Take out the commercial nickel-molybdenum foam after electrochemical treatment, rinse with deionized water, and place it in a 40°C oven for drying. The sample is marked as NMFeS (where NM represents nickel-molybdenum substrate, Fe represents ferric chloride hexahydrate, and S represents sodium thiosulfate pentahydrate). The ratio of each specific parameter in Example 1 is shown in Table 1.

[0031] Table 1 Detailed list of experimental parameters

[0032]

[0033] Comparative Example 1

[0034] The difference between this comparative example and Example 1 is that commercial nickel-molybdenum foam is treated with only an aqueous solution of 0.1 mol / L ferric chloride hexahydrate, and after corrosion at 40°C for 1 hour, the metal substrate is rinsed with deionized water and placed in a 40°C oven for drying. The sample is marked as NMFe (Fe represents ferric chloride hexahydrate, and NM represents a commercial nickel-molybdenum foam substrate). The ratio of each specific parameter in Comparative Example 1 is shown in Table 2.

[0035] Table 2 Detailed list of experimental parameters

[0036]

[0037] Comparative Example 2

[0038] The difference between this comparative example and Example 1 is that commercial nickel-molybdenum foam is treated with an aqueous solution of sodium thiosulfate pentahydrate with a concentration of 0.05 mol / L, and after corrosion at 40°C for 1 hour, the metal substrate is rinsed with deionized water and placed in a 40°C oven for drying. The sample is marked as NMS (S represents sodium thiosulfate pentahydrate, and NM represents commercial nickel-molybdenum foam substrate). The ratio of each specific parameter in Comparative Example 2 is shown in Table 3.

[0039] Table 3 Detailed list of experimental parameters

[0040]

[0041] Comparative Example 3

[0042] The difference between this comparative example and Example 1 is that the commercial nickel-molybdenum foam substrate (NMF) is not subjected to any treatment and is marked as NMF. The proportions of the specific parameters in Comparative Example 3 are shown in Table 4.

[0043] Table 4 Detailed list of experimental parameters

[0044]

[0045] Test example

[0046] 1.CV, LSV and EIS tests

[0047] Taking the NMFeS catalytic material in Example 1 as an example, a performance test was carried out.

[0048] The test process is as follows: In 1M / L KOH solution, a standard three-electrode system is used, the counter electrode is a platinum sheet (10mm*10mm*0.1mm), Hg / HgO is used as the reference electrode, and the commercial nickel-molybdenum foam substrate treated with ferric chloride hexahydrate and sodium thiosulfate pentahydrate is used as the working electrode. At room temperature, the electrochemical detection is carried out using the Wuhan Koster electrochemical workstation.

[0049] Table 5 shows the overpotential measurement results of Example 1 and Comparative Examples 1-3.

[0050] Table 5 Oxygen evolution overpotential test table

[0051]

[0052]

[0053] Figure 1 2 is the LSV curve diagram of each experimental sample. It can be observed from the figure that the performance of NMFeS is significantly better than that of comparative examples 1-3.

[0054] Figure 2The overpotential comparison diagram of each experimental sample shows that the overpotential of each sample increases with the increase of current density, but at the same current density, the overpotential of NMFeS remains the lowest. -2 When the overpotential is only 261mV, it is lower than NMF at 10mA cm -2 The overpotential under (333mV).

[0055] Figure 3 This is the constant potential polarization curve of NMFeS in 1M / L KOH solution. It can be concluded from the figure that the current density of NMFeS can be basically stable at 1Acm -2 And after 1466 hours of operation, the performance remained basically the same, reflecting that NMFeS has excellent structural stability.

[0056] Figure 4 The electrochemical impedance spectroscopy (EIS) comparison diagram of each sample at a DC potential of 0.53V (relative to Hg / HgO) shows that compared with other samples, NMFeS has the smallest semicircle diameter, the lowest charge transfer resistance and the lowest diffusion resistance. This phenomenon indicates that under the combined action of sodium thiosulfate pentahydrate and ferric chloride hexahydrate, the diffusion resistance of the nickel-molybdenum substrate is reduced and the electron transfer rate of the nickel-molybdenum substrate is accelerated. The excellent charge transfer ability of NMFeS is the key factor for its excellent OER activity.

[0057] 2. Microstructure and chemical properties

[0058] Taking NMFeS in Example 1 as an example, its microstructure and chemical properties are analyzed. The specific results are shown in Figure 5-Figure 6 .

[0059] Figure 5 This is a SEM image of a commercial metal substrate (nickel-molybdenum foam) after being corroded by ferric chloride hexahydrate and sodium thiosulfate pentahydrate. The passive film on the surface of the treated substrate is completely destroyed, forming a small and uniform flaky crystal film layer, which expands the electrochemical surface area, provides more reactive sites, and forms abundant electron transport channels, which is conducive to enhancing OER activity.

[0060] Figure 6This is the element distribution map of NMFeS. According to the TEM mapping results, the atomic ratios of nickel, iron, molybdenum, oxygen and sulfur in the nickel-molybdenum catalytic material are 15-35:2-10:0-1:60-75:0-3. The TEM test used a processed sample and mounted it on a copper mesh for detection. The use of a copper mesh reduces interference with elemental analysis, making the results more reliable and accurate. TEM can provide higher resolution and more detailed element distribution information, so its results are generally considered to be more representative. Therefore, it can be inferred that the true atomic ratio of nickel, iron, molybdenum, oxygen and sulfur in the NMFeS sample is approximately 15-35:2-10:0-1:60-75:0-3.

[0061] The above analysis shows that the nickel-molybdenum catalytic material provided by the present invention can quickly corrode the surface of the commercial metal substrate (nickel-molybdenum foam) to form a unique flaky crystalline film structure, showing excellent OER performance.

[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A nickel-molybdenum catalytic material, characterized in that: The nickel-molybdenum catalytic material is obtained by treating ferric chloride hexahydrate and sodium thiosulfate pentahydrate; According to the TEM-mapping element distribution analysis, the atomic ratios of nickel, iron, molybdenum, oxygen and sulfur in the nickel-molybdenum catalytic material are 15~35:2~10:0~1:60~75:0~3.

2. The nickel-molybdenum catalytic material according to claim 1, characterized in that: The crystalline layer includes at least one of features (A1) to (A3): (A1) Crystals are in the form of flakes, needles or strips; (A2) Crystallization forms a thin film covering the surface of the metal substrate; (A3) The crystals are covered on the substrate surface through non-covalent bonding.

3. A method for preparing a nickel-molybdenum catalyst material as claimed in claim 1 or 2, characterized in that: The steps include: The metal substrate is corroded by a treatment solution, and the corroded metal substrate is used as a working electrode. The nickel-molybdenum catalytic material is obtained by electrochemical treatment in a standard three-electrode system; the treatment solution is a mixed solution of ferric chloride hexahydrate and sodium thiosulfate pentahydrate.

4. The method for preparing the nickel-molybdenum catalyst material according to claim 3, characterized in that: The size of the metal substrate used is approximately 15 mm long × 10 mm wide × 1.5 mm high.

5. The method for preparing the nickel-molybdenum catalytic material according to claim 3, characterized in that: Three-electrode system: the treated metal substrate is the anode, Hg / HgO is the reference electrode, the platinum sheet is the counter electrode, and potassium hydroxide is the electrolyte.

6. The method for preparing the nickel-molybdenum catalytic material according to claim 3, characterized in that: Electrochemical treatment: The working electrode was scanned for 1 to 5 cycles using cyclic voltammetry in a voltage window of 0 to 1 V.

7. The method for preparing the nickel-molybdenum catalytic material according to any one of claims 3 to 5, characterized in that: The addition ratio of ferric chloride hexahydrate to sodium thiosulfate pentahydrate is 0.1M / L:0.05M / L.

8. The method for preparing the nickel-molybdenum catalytic material according to any one of claims 3 to 5, characterized in that: Corrosion treatment: Corrosion treatment in 40℃ treatment solution for 1h.

9. Application of the nickel-molybdenum catalytic material as claimed in claims 1 to 3, or the nickel-molybdenum catalytic material obtained by the preparation method as claimed in any one of claims 4 to 8 in a test of electrolytic hydrogen production.